2020
DOI: 10.1113/ep088339
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent reloading does not prevent reduction in iron availability and hepcidin upregulation caused by hindlimb unloading

Abstract: In humans, exposure to microgravity during spaceflights causes muscle atrophy, iron storage changes, and iron availability reduction. We previously observed in rats that during simulated microgravity for 7 days, hepcidin plays a key role in iron misdistribution, and suggested that a crosstalk between skeletal muscle and liver could regulate hepcidin synthesis in this context. In the present study, we investigated in rats the medium-term effects of simulated microgravity on iron metabolism. We also tested wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
8
0
4
Order By: Relevance
“…Using the hind limb unloading (HU) model to simulate the microgravity in rats, we recently showed that short‐term exposure to HU causes iron misdistribution, characterized by increased splenic iron store 8 . Interestingly, hepatic hepcidin expression and blood hepcidin levels increase in rodents exposed to simulated microgravity 8‐10 . As hepcidin controls iron release from cells, especially spleen macrophages, it could play a key role in microgravity‐induced iron misdistribution by limiting the expression and activity of ferroportin, the cell iron exporter that allows iron recycling from macrophages in plasma 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Using the hind limb unloading (HU) model to simulate the microgravity in rats, we recently showed that short‐term exposure to HU causes iron misdistribution, characterized by increased splenic iron store 8 . Interestingly, hepatic hepcidin expression and blood hepcidin levels increase in rodents exposed to simulated microgravity 8‐10 . As hepcidin controls iron release from cells, especially spleen macrophages, it could play a key role in microgravity‐induced iron misdistribution by limiting the expression and activity of ferroportin, the cell iron exporter that allows iron recycling from macrophages in plasma 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Afin de répondre en partie au premier objectif précédemment énoncé, nous avons relancé un protocole de suspension par la queue sur une période plus longue de 14 jours. Nous avons ainsi observé que la rate n'était plus surchargée en fer sur une période plus longue d'hypoactivité, malgré une réduction persistante de la biodisponibilité du fer [31]. Ces résultats suggèrent donc que le fer est toujours anormalement distribué à plus long terme, mais que les organes impactés…”
Section: La Distribution Du Fer Dans L'organisme éVolue Selon La Durée D'exposition à L'hypoactivitéunclassified
“…c c e p t e d m a n u s c r i p t ne sont pas nécessairement les mêmes. Le foie et le muscle squelettique atrophié ne seraient pas les cibles de cette surcharge au regard de l'absence de changements des concentrations en fer chez les animaux suspendus par la queue[31]. De manière intéressante, des travaux conduit parallèlement aux nôtres ont observé chez le rongeur que le foie et l'os commencent à être surchargés en fer après une plus longue période d'hypoactivité (i.e.…”
unclassified
See 1 more Smart Citation
“…Hindlimb unloading is one of the models employed to study the effects of microgravity on musculo‐skeletal physiology. Nay and colleagues address the question of whether skeletal muscle is involved in microgravity‐induced iron misdistribution by modulating the expression of hepcidin, and whether intermittent reloading is of benefit in this regard (Nay et al., 2021). One of the major, as yet unsolved, problems to be faced by those exposed to long periods of microgravity is the visual disturbances collectively known as space flight‐associated neuro‐ocular syndrome (SANS).…”
mentioning
confidence: 99%